Parametric design of a turtle rehabilitation centre - Abdullah, Fadzidah; Shaharudin, Muhamad Izhar; Yusof, Zeenat Begam; Azmin, Aida Kesuma; Sanusi, Aliyah Nur Zafirah; Asif, Nayeem (Asia International Community of Art & Design (AICAD), Faculty of Art & Design,Universiti Teknologi MARA, 2022)
An architect’s dream is often regarded as an engineer’s nightmare, especially when dealing with architecture that requires challenging amalgamation of structure and sculpture. Often, the so-called parametric design could only be realised when the designer uses high-end computer aided design software. Nevertheless, with critical algorithmic exploration of forms, parametric architectural design could be manually crafted, producing lucrative and inspirational architecture. This project had two (2) objectives: to critically explore algorithmic 3-dimentional forms for parametric architectural design, and to produce the best possible architectural design solution for a Turtle Rehabilitation Centre. Qualitative approach of an action research was carried out, to systematically observe and consult the designer when he underwent the experiential exploration of forms to solve design problems and constraints. The designer managed to produce a design scheme that is not only visually stimulating, but also could implant the feeling of stewardship towards sustainability among the public.